Hubungan Dukungan Keluarga, Tingkat Pendidikan dan Usia dengan Kepatuhan dalam Pembatasan Asupan Cairan pada Klien ESRD yang Menjalani Terapi Hemodialisa - Andri Kusuma Wijaya; Padila Padila (Jurnal Keperawatan Silampari, 2019)
This study aims to determine the relationship of family support, education level and age to adherence in limiting fluid intake in End Stage Renal Disease clients undergoing hemodialysis therapy at Dr. M Yunus Hospital Bengkulu. This study uses a cross sectional design, with a total sample of 108 respondents. The results of the analysis proved to be a relationship between family support (p value = 0, 000) with adherence to restrictions on fluid intake, while education level variables (p value = 0.762) there was no relationship with adherence to restrictions on fluid intake, while for age variables (p value = 0.728) there was also no relationship with adherence to fluid intake restrictions. Family support is very important to be considered as one of the supporting factors to increase compliance in limiting fluid intake to clients undergoing hemodialysis therapy, so it is expected that family support can be maximized in giving to create behavior that complies with limiting fluid intake by being informed to the family especially through the organization of hemodialysis clinics that always serve End Stage Renal Disease clients who undergo hemodialysis therapy. Keywords : ESRD, IDWG, Adherence